APPLICATION OF STUDENTS' TECHNOLOGY ADAPTATION THROUGH THE TEACHING CAMPUS PROGRAM AT SD NEGERI DURIKULON - Lande , Adriani; Darmayanti, Novi; Mutia, Khusnul (Journal of Social Comunity Services, 2024)
Objective: This study examines the impact of the Teaching Campus Program, part of the Independent Learning Independent Campus (MBKM) initiative by the Ministry of Education, Culture, Research, and Technology, on technology adaptation in elementary schools, focusing on SD Negeri Durikulon Laren Lamongan, where technology adaptation skills are limited. Methods: A qualitative descriptive approach was used, involving observation and coordination with school stakeholders, the introduction and practice of technology use, and a series of evaluations. Result: The program facilitated students’ understanding of computer hardware and basic applications, specifically Microsoft Word, enhancing both teacher and student technology adaptability. The activities, organized in a four-month cycle, provided hands-on experiences that directly supported teaching and learning processes. Novelty: This study highlights the MBKM’s role in creating practical learning environments outside traditional classrooms, contributing a model of how university students can aid in technology adaptation at the elementary level. The findings suggest a positive impact on all participants, laying the groundwork for continued implementation of similar programs to support technology readiness among young students across Indonesia.